Cultivating Health in Martial Arts and Combat Sports Pedagogies: A Theoretical Framework on the Care of the Self - Pedrini, Lorenzo; Jennings, George (Frontiers in Sociology, 2021)
“Martial arts and combat sports” (MACS) are a myriad of systems of embodied movements and underlying philosophy and pedagogies. Due to the intrinsic complexity of MACS, they have the potential to both reshape practitioners’ selves and improve their wellbeing, as well as to hamper the pursuit of sustainable, healthy lifestyles. This article provides an interdisciplinary theoretical framework to critically approach both the “light” and the “dark” sides of martial pedagogies. The model we propose develops the Foucauldian notion of “the care of the self,” which has been considerably overlooked in martial arts scholarship. Furthermore, by viewing health as a goal for cultivation, this proposal places the situated practices linked to materiality and discourses at the centre of the theoretical and empirical analyses. The article thus takes into account the internal diversity and cross-institutional variance of martial pedagogies by allowing scholars to explore four forms of cultivation (self, shared, social, ecological) prompted on a day-to-day basis. To conclude, we discuss the main methodological implications for multimodal research arising from the framework in order to foster future inquiries.